Multi-locational evaluation of cooking banana cultivars ‘NARITA 4’ hybrid and ‘Mpologoma’ in Rwanda - Ndayitegeye, O.; Blomme, Guy; Ocimati, W.; Crichton, R.; Ntamwira, J.; Muchunguzi, P.; Asten, Piet J.A. van; Bahati, L.; Gaidashova, S.V. (Academic Journals, 2017)
This study assessed the growth and yield of two introduced cooking banana cultivars ‘Mpologoma’ and ‘NARITA 4’ relative to seven local highland cooking cultivars, across three sites in Rwanda, namely Karongi (1496 m a.s.l.), Gatore (1523 m a.s.l.) and Rwinzuki (1671 m a.s.l.). Data were obtained during two cropping cycles (plant crop cycle and the 1st ratoon). Data on pseudostem girth (cm) at 100 cm above the ground was collected at flowering, while number of hands per bunch, number of fingers of the second lowest hand and bunch weight (kg) were obtained at bunch harvest. Significant differences for all assessed growth and yield parameters were observed between cultivars (p<0.001). Generally, the two exotic cultivars ranked high with respect to number of fingers on the second lowest hand and number of hands per bunch. ‘Mpologoma’ had the largest bunch with a mean bunch weight of 23 kg, whereas ‘NARITA 4’ had a bunch weight of 17 kg which was comparable to the local cultivars. Thus, these 2 cultivars could potentially be adopted by farmers.